INDIGENOUS USES AND PHYTOCHEMICAL CONTENTS OF PLANTS USED IN THE TREATMENT OF MENSTRUAL DISORDERS AND AFTER- CHILD BIRTH PROBLEMS IN ABEOKUTA SOUTH LOCAL GOVERNMENT AREA OF OGUN STATE, NIGERIA - Kadiri, M; Ojewumi, A W; Onatade, T N (Journal of Drug Delivery and Therapeutics, 2015)
A survey of plants used for the treatment of menstrual disorders and after-child birth problems was conducted in Abeokuta South Local Government. Hundred (100) questionnaires were administered using multi stage sampling method on traditional herbal practitioners. Ethnobotanical information such as, plants and plant parts used, methods of extraction used and mode of administration of the herbal preparations of these plants were requested. Also, phytochemical contents of the most frequently mentioned plants were determined. Data were subjected to Analysis of variance (ANOVA) with probability set at p<0.05 and descriptive statistics. Results revealed that a total of fifty-six (56) plants belonging to 37 families were mentioned. The most frequently mentioned families are Euphorbiaceae, Leguminoceae, Anacardiaceae, Apocynaceae, Araceae and Combretaceae. Sesamum indicum, Dioclea sarmentosa, Clausena anisata, Anogeissus leiocarpus, Alafia barteri, Tetrapleura tetraptera, Daniella oliveri, Lannea egregia and Alstonia boonei were the most frequently mentioned plants used in the treatment of menstrual disorders and after-childbirth problems. Leaves (34%), fruits (7%), flowers (3%), tubers (2%), stem-barks (28%), seeds (11%) , roots and barks (2%) and roots (13%) were the plantsÂ reported being used for the remedy of these disorders. Decoction (54%), squeezing (9%), grinding/squeezing (14%), paste (4%), exudation (4%), cooking (4%), soaking/ decoction/infusion (4%), and heating to ashes (4%) were the methods of extracting the bioactive principles of the plants using water (79%) as major solvent. Significant difference (P < 0.05) was observed in the quantities ofÂ Â tannins recorded in the leaves of Sesamun indicum, Dioclea sarmentosa, Clausena anisata, Anogeissus leiocarpus and Alafia barteri. Similar observations were found in the quantities of saponnins, alkaloids, flavonoids and phenol. Highest values of tannins (0.32mg/g), saponnins (1.07mg/g), alkaloids (5.16mg/g), flavonoids (3.12mg/g) and phenol (0.09 mg/g) were determined in the leaves ofÂ Â Clausena anisata, Sesanum indicum, Dioclea sarmentosa and Alafia barteri. Across the roots of these plants, similar amount of tannins and saponnins were quantified. This observation varied significantly when compared with alkaloids, flavonoids and phenol quantified in the roots of plants. Highest tannins (1.67mg/g) and saponnins (3.33 mg/g) were recorded in the roots of Dioclea sarmentosa, alkaloids (4.33 mg/g) and flavonoid (6.33 mg/g) in Anogeissus leiocarpus while phenol (1.33 mg/g) was recorded in roots of Sesanum indicum. Â Key words:Â Menstrual Disorders, Childbirth Problems, phytochemical contents, Traditional practitioners, Indigenous plants